2022
DOI: 10.1136/bmjopen-2022-063653
|View full text |Cite
|
Sign up to set email alerts
|

Income precarity and child and parent weight change during the COVID-19 pandemic: a cross-sectional analysis of the Ontario Parent Survey

Abstract: ObjectivesTo describe child and parent weight change during the pandemic, overall and by income precarity.DesignA cross-sectional online survey was conducted.SettingCaregivers of children 0–17 years of age living in Ontario, Canada, during the COVID-19 pandemic from May 2021 to July 2021.ParticipantsA convenience sample of parents (n=9099) with children (n=9667) living in Ontario were identified through crowdsourcing.Primary outcome measureParents recalled, for themselves and their child, whether they lost wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our findings are consistent with at least one other study conducted prior to the pandemic which found that financial stress was associated with a higher prevalence of weight gain in the US, especially among those experiencing difficulty paying bills or who had less money to meet life necessities [ 5 ]. A Canadian study conducted during the pandemic also found that financial hardship was strongly associated with both weight loss and weight gain [ 6 ]. Although there is minimal evidence on the association between financial hardship and weight change during the pandemic in the US, one study did find that economic stress during the pandemic was linked to increases in unhealthy behaviors (less exercise, sleep, and healthy eating; more smoking/vaping and drinking alcohol), which could lead to weight change [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with at least one other study conducted prior to the pandemic which found that financial stress was associated with a higher prevalence of weight gain in the US, especially among those experiencing difficulty paying bills or who had less money to meet life necessities [ 5 ]. A Canadian study conducted during the pandemic also found that financial hardship was strongly associated with both weight loss and weight gain [ 6 ]. Although there is minimal evidence on the association between financial hardship and weight change during the pandemic in the US, one study did find that economic stress during the pandemic was linked to increases in unhealthy behaviors (less exercise, sleep, and healthy eating; more smoking/vaping and drinking alcohol), which could lead to weight change [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Financial hardship has the potential to impact weight change (e.g., stress-related overeating, food insecurity) [ [5] , [6] , [7] ] and the long-term health effects of weight change (e.g., increased risk of morbidity and mortality) [ [8] , [9] , [10] ]. Prior to the pandemic, financial hardship has been associated with both an increased risk of weight loss and weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study was conducted using data from the Ontario Parent Survey 2 between May 4 th and July 3 rd , 2021 [ 26 , 27 ]. Caregivers and parents (hereafter collectively referred to as parents) of children 5–17 years of age in Ontario, Canada were recruited to participate in the voluntary, open, online survey.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study was conducted using data from the Ontario Parent Survey 2 between May 4 th and July 3 rd , 2021 [26,27]. Caregivers and parents (hereafter collectively referred to as PLOS ONE html) awarded to AG.…”
Section: Study Design and Samplingmentioning
confidence: 99%
“…Moreover, theoretical models highlighted that parental health is correlated with the health of children and vice versa (Joshi et al, 2023). Although negative strategies used by the parents may cause significant harm to children and cause issues severe psychological and behavioral issues (Zafar et al, 2021).…”
Section: Research Backgroundmentioning
confidence: 99%